Effectiveness of Non-invasive Interventions in Managing Cardiovascular Disease Using Specific Biological Markers - Bansal, Dheeraj; Chuchulo, Anastasya (Indian Journal of Community Health, 2018)
Background: Lifestyle interventions consisting of diet, exercise, psychosocial support and stress management are a clinically effective alternative to the management of cardiovascular diseases that can be feasibly measured and monitored during treatment using various biological markers. Methodology: A thorough Pubmed search was conducted looking for the results of articles that treated cardiovascular disease patients of both sexes and all ages with lifestyle modification in which the effectiveness of lifestyle modification was measured by various biomarkers. Results: The final review was conducted on 11 journal articles that were found examining exercise, diet, psychosocial support and stress management in cardiovascular disease patients and showing a positive benefit of such an intervention and the effects on biomarkers as an alternative to traditional pharmacological treatment. The affected biomarkers found were percent diameter coronary artery stenosis, blood pressure, cholesterol, body weight and fat, heart rate, HbA1c, exercise capacity, C reactive protein, triglycerides and BMI. Conclusion: Lifestyle modification consisting of exercise, low fat, high complex carbohydrate diet, psychosocial support and stress management is clinically efficacious in the treatment of cardiovascular disease as seen by the various changes in biological measures.